Effect of Nitrogen on Growth and Yield of Knol Khol Varieties in Chitwan - Adhikari, Janjit; Karki, Ashmita; Giri, Hom Nath; Shrestha, Arjun Kumar; Srivastava, Arvinda (Multi-Disciplinary Explorations: The Kasthamandap College Journal, 2023)
Available with the full text.